Perfil do consumo alimentar e imagem corporal em jogadoras de futsal - PINTO, Kassiandra Lima (2023)
Objective: To identify the nutritional and behavioral profile in female futsal players. Materials and Methods: 22 female adult female futsal players from Moto Club were evaluated, the procedures evaluated were training time in years, training time in days of the week and training time in hours per day; Self-reported anthropometric assessment of age, weight and height; Body Mass Index Classification; Identification of time of schooling; Socioeconomic classification; Assessment of food consumption; Body Image Assessment. Results: Mean age was 27.87 ±4.68. Body weight averaged 62.38 ±10.77 and height averaged 1.62 ±0.07. In relation to the body mass index, 59% of the sample were eutrophic, 23% overweight, 9% in a state of thinness and obesity grade I. Regarding schooling, 18% had completed high school, 5% had incomplete high school, 36% have incomplete higher education, 32% have completed higher education, 9% have a master's or graduate degree. Regarding the practice time, 86% of the players reported that they train more than 3 years, 45% train twice a week, 55% train more than 2 hours and less than 3 hours. Regarding socioeconomic stratification, 36% belong to class B, 32% belong to Class C1, 18% belong to Class B1, 9% belong to class C2 and 5% belong to class A. Regarding food consumption on Sunday, energy value total in kcal was on average 1854 ±744.91, average carbohydrate consumption was 201.05 ±89.54, in percentage was on average 43.87 ±9.93. As for protein, the average consumption was 91.20 ±8.03, in percentage its value was 21.10 ±8.03, the average intake of lipids was 74.04 ±41.18, in percentage the value obtained was 35.02 ±9.81. In relation to body image, when the players were evaluated by the silhouette scale, 18% were satisfied with their body image, 68% were dissatisfied with their excess weight and 14% were dissatisfied with their thinness. Conclusion: The studied sample presented in mostly eutrophic nutritional status, with incomplete higher education, with dissatisfaction with their self-perception of body image. As for their food consumption, they presented a profile of a hypoglycemic, hyperproteic and normolipidic diet. Thus, it is concluded that futsal players need nutritional monitoring so that they can have a balanced diet.